Attentional variability and avoidance of hostile stimuli decrease aggression in Chinese male juvenile delinquents - Ziyi Zhao; Xianglian Yu; Zhihong Ren; Lin Zhang; Xu Li (BMC, 2021)
Abstract Background As a prominent issue worldwide, juveniles' aggressive and violent crimes have attracted much interest in recent years. Based on the social information processing model, the present study aimed to evaluate the Chinese male juvenile delinquents' attention bias towards hostile stimuli from both static and dynamic perspectives. Additionally, the predictive effect of attention bias on aggressive behavior and the moderating effect of group (juvenile delinquents and the controls with no criminal history) were also investigated. Methods The hostile attention bias and aggressive behavior of 76 juvenile delinquents (M age = 17.5 years, SD = 0.59 years) and 67 controls (M age = 18.3 years, SD = 0.73 years) were measured with the emotional dot-probe task, emotional Stroop task, and the Chinese version of the Buss & Perry aggression questionnaire, respectively. Results The results showed that compared with controls, juvenile delinquents showed more attention biases towards hostile faces and words, and demonstrated higher levels of physical aggression and anger. Furthermore, the type of participants moderated the relationship between hostile attention bias and aggressive behavior. For juvenile delinquents, attention bias away from hostile stimuli and attention variability negatively predicted anger, while for controls, attention variability positively predicted self-directed aggression. Conclusion Attentional variability and avoidance of hostile stimuli are expected to reduce the aggressive level of Chinese male juvenile delinquents. The relationship between attention bias and aggression should be further considered and applied in the clinical practice.